-selfadjoint product of a composition operator and a maximal differential operator on the Fock space. Issue 11 (2nd November 2022) - Haji Shaabani, Mahmood; Baseri Nezhad, Mohammad; Viet Hai, Pham
Abstract : In this paper, we are interested in operators arising from the product of a weighted composition operator and a maximal differential operator on the Fock space. Let T max and C u, φ denote a maximal differential operator and a weighted composition operator, respectively. We characterize some C -selfadjoint operators C u, φ T max with respect to special conjugations C . Moreover, we obtain a partial characterization of hermitian operator C φ T max .